Epiphanies at the Supermarket: An Interview with Brigitte Kronauer - Jutta Ittner (Studies in 20th & 21st Century Literature, 2003)
Brigitte Kronauer has been called "the greatest German [female] fiction writer of our time" (Marcel Reich-Ranicki). Her stories, novels, and criticism have established her as a uniquely sophisticated literary voice and won her many literary prizes. Kronauer's trademarks are her laser-sharp vision, her luminous prose, and the intricate structures of her uncannily realistic literary universes. Finding the mystical in the mundane and exposing human foibles with subtle irony, Kronauer creates, in the words of one critic, epiphanies at the supermarket. Beneath its everyday surface her fiction deals with the eternal human questions of life, death, and love. At a still deeper level it circles around philosophical issues such as our futile attempts to find truth in our own constructs of reality. In her interview with Jutta Ittner the author reflects on her individual path to writing. She describes the role of literature in creating a semblance of order in a multifaceted reality, and she discusses the structure of her literary universes, her characters and their aspirations, and the importance of animals for man's quest for a meaningful life. Finally, Kronauer explains how she sees herself in terms of women's literature and indicates where her writing is headed.
Keywords: Brigitte Kronauer; greatest German [female] fiction writer; Marcel Reich-Ranicki; stories; novels; criticism; vision; prose; structures; realistic; universe; mystical in the mundane; mundane; mystical; irony; subtle irony; futile; reality; construct; Jutta Ittner; interview; writing; literature; animals; animal; man; meaningful life; women& #x27; s literature